Thermal Radiation Effects on Stagnation Point Flow Past a Stretching/Shrinking Sheet in a Maxwell Fluid With Slip Condition - Nazila, Ishak; Hasmawani, Hashim; Muhammad Khairul Anuar, Mohamed; Norhafizah, Md Sarif; Norhayati, Rosli; Mohd Zuki, Salleh (IOP Publishing, 2017)
In this study, the numerical solution of the thermal radiation effects on a stagnation point flow past a stretching/shrinking sheet in a Maxwell fluid with slip condition is considered. The transformed boundary layer equations are solved numerically using the Runge-Kutta-Fehlberg (RKF) method. Numerical solutions are obtained for the skin friction coefficient and the wall temperature as well as the temperature and the velocity profiles. The features of the flow and the heat transfer characteristics for various values of Prandtl number, stretching/shrinking parameter, thermal radiation parameter, Maxwell parameter, dimensionless velocity slip parameter and thermal slip parameter are analyzed and discussed.